2016
DOI: 10.1039/c6ra21293j
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of gas adsorption on silicene nanoribbons and its application in a highly sensitive molecule sensor

Abstract: Inspired by the recent successes in the development of two-dimensional based gas sensors capable of single gas molecule detection, we investigate the adsorption of gas molecules (N2, NO, NO2, NH3, CO, CO2, CH4, SO2, and H2S) on silicene nanoribbons (SiNRs) using density functional theory (DFT) and nonequilibrium Green's function (NEGF) methods. The most stable adsorption configurations, adsorption sites, adsorption energies, charge transfer, quantum conductance modulation, and electronic band structures of all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 87 publications
7
50
0
Order By: Relevance
“…Inspired by the astonishing gas sensing performance of graphene, the sensing capability of other 2D structures such as MoS 2 [26,27], WS 2 [28,29], phosphorene [30,31], boron nitride [32,33], silicene [34,35], and germanene [36] toward various gases have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the astonishing gas sensing performance of graphene, the sensing capability of other 2D structures such as MoS 2 [26,27], WS 2 [28,29], phosphorene [30,31], boron nitride [32,33], silicene [34,35], and germanene [36] toward various gases have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There have been myriad theoretical and experimental studies on adsorption of H 2 S on metal surfaces, 7,8 transition metal oxides, 9 mixed oxides, 10 zeolites, 11 polymers, 12 carbonaceous materials, [13][14][15] and silicon-based materials. [16][17][18] Since the discovery of fullerene in 1985, the search for heteroatomic spherical fullerene-like structures based on noncarbon inorganic materials has been a hot topic. 19 Strout et al found that among all (XY) n fullerene-like nanocages, X 12 Y 12 cages are the most stable ones.…”
Section: Funding Information Iran Nanotechnology Initiative Councilmentioning
confidence: 99%
“…Thereupon, the adsorption of H 2 S on activated surfaces as an initial condition for sulfurization is of great importance. There have been myriad theoretical and experimental studies on adsorption of H 2 S on metal surfaces, transition metal oxides, mixed oxides, zeolites, polymers, carbonaceous materials, and silicon‐based materials …”
Section: Introductionmentioning
confidence: 99%
“…Low-dimensional nanomaterials have shown great capabilities in single-molecule detection. Two-dimensional nanomaterials like graphene, [22][23][24][25][26][27][28] silicene, [29,30] germanene, [31,32] hexagonal boron nitride, [33] MoS 2 [28,34,35] and WS 2 , [28,36] one-dimensional nanomaterials such as carbon nanotubes (CNTs), [22,[37][38][39][40] boron nitride nanotubes [41] and silicene nanoribbons, [42,43] and zero-dimensional nanomaterials such as fullerene-like X 12 Y 12 nanocages [44][45][46][47][48][49] have been extensively explored as sensor materials for the sensing of various molecules. Ramraj et al studied the interactions between nucleic acid bases with graphene and CNTs through quantum chemical methods.…”
Section: Introductionmentioning
confidence: 99%